Tantangan Pembelajaran Pendidikan Agama Islam di Era Digital - Dyah Farissa; Budi Haryanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research discusses the learning challenges of Islamic Religious Education (PAI) in the digital era, with a focus on improving teacher competence, material relevance, and students' readiness to face technological developments. The research method used is library research with content analysis and a hermeneutic approach to understand the contextual meaning of various sources. The results of the study show that digitalization brings significant changes in the PAI learning process, starting from a paradigm that shifts from conventional methods to technology-based learning, to the use of digital media to support the teaching and learning process. However, there are challenges such as low digital literacy, technology access gaps, potential internet abuse, and the need for innovation in the preparation of teaching materials to remain relevant and effective. This research emphasizes the importance of strengthening teacher competence, developing digital learning materials, and improving students' digital literacy to ensure that PAI learning is still able to shape the character and spiritual values of the younger generation in the midst of changing times.